Effect of 12-month intervention with low-dose atorvastatin on pulse wave velocity in subjects with type 2 diabetes and dyslipidaemia. (January 2019) - Grigoropoulou, Pinelopi; Tentolouris, Anastasios; Eleftheriadou, Ioanna; Tsilingiris, Dimitrios; Vlachopoulos, Charalambos; Sykara, Maria; Tentolouris, Nikolaos
Cardiovascular disease is the leading cause of morbidity and mortality in subjects with type 2 diabetes mellitus. Increased aortic stiffness, assessed with the carotid–femoral pulse wave velocity, is an independent risk factor for cardiovascular disease. Statins reduce effectively cardiovascular disease and mortality in high-risk patients. The aim of this prospective non-randomized, observational study was to examine the impact of treatment with either 10 mg atorvastatin plus diet or diet alone on carotid–femoral pulse wave velocity in subjects with type 2 diabetes mellitus and dyslipidaemia. A total of 79 subjects with type 2 diabetes mellitus and dyslipidaemia were included; 46 subjects were treated with atorvastatin 10 mg daily plus diet and 33 were managed by diet alone for 12 months. Carotid–femoral pulse wave velocity and carotid–radial pulse wave velocity were measured using applanation tonometry. In the atorvastatin-treated group, carotid–femoral pulse wave velocity reduced significantly during the study and there was a trend for reduction in the carotid–radial pulse wave velocity. Total cholesterol, low-density lipoprotein cholesterol, triglycerides and C-reactive protein were reduced only in the atorvastatin-treated participants. No significant changes were found in body mass index, blood pressure, heart rate, diabetes control and high-density lipoprotein cholesterol in either study group. Treatment with low-dose atorvastatin for 12 months improves carotid–femoral pulse wave velocity in subjects with type 2 diabetes mellitus and dyslipidaemia.